18F-AlF-NOTA-octreotide PET/CT in the localization of tumor-induced osteomalacia: case series and literature review - Li, Jing (Frontiers in Endocrinology, 2024)
This study explores tumor-induced osteomalacia (TIO) through a case series and literature review, assessing the diagnostic potential of 18 F-AlF-NOTA-octreotide ( 18 F-OC) positron emission tomography/computed tomography (PET/CT).We analyzed TIO patients who underwent 18 F-OC PET/CT. Parameters such as tumor dimension, the maximum standardized uptake value (SUVmax), the mean standardized uptake value (SUVmean) and metabolic tumor volume (MTV) were meticulously assessed. Clinical features and imaging characteristics pertinent to TIO were reviewed.Results: 6 patients with clinical suspicion of TIO exhibited hypophosphatemia (0.25 to 0.64 mmol/L), elevated alkaline phosphatase (ALP) levels (142 to 506 U/L), and increased parathyroid hormone (PTH) levels (92.9 to 281.7 pg/mL). Of these patients, two underwent FGF-23 testing, with results of 3185.00 pg/ml and 17.56 pg/ml, respectively. Conventional imaging modalities depicted widespread osteoporosis, with several cases demonstrating fractures indicative of osteomalacic and associated pathological fractures. Subsequent 18 F-OC PET/CT facilitated the accurate localization of causative tumors, with histopathological examination confirming the diagnosis of phosphaturic mesenchymal tumor (PMT). The interval from initial clinical presentation to definitive TIO diagnosis spanned approximately 2.5 years (range: 1 -4 years), with tumors varying in size (maximum diameter: 7.8 to 40.0 mm), SUVmax (5.47 to 25.69), SUVmean (3.43 to 7.26), and MTV (1.27 to 18.59 cm 3 ).The implementation of whole-body 18 F-OC PET/CT imaging emerges as a critical tool in the identification of occult tumors causing TIO. Future investigations incorporating a broader cohort are imperative to further delineate the diagnostic and therapeutic implications of 18 F-OC PET/CT in managing TIO.